Answer:
C
Explanation:
We can use 3 properties here to write this as single logarithm:
1. Log (a^b) = b Log a
2. Log x + Log y = Log (x*y)
3. Log x - Log y = Log (x/y)
We can use property #1 first to write:
![ln2x+2lnx-ln3y\\=ln2x+lnx^2-ln3y](https://img.qammunity.org/2020/formulas/mathematics/high-school/6wyt58t03n83i0ryoqlbk1kpllq9ee1i9o.png)
Now we can use property #2 and property #3 to write this as single logarithm:
![ln2x+lnx^2-ln3y\\=ln(((2x)(x^2))/(3y))\\=ln((2x^3)/(3y))](https://img.qammunity.org/2020/formulas/mathematics/high-school/tcn2wh86k7wlk5cdpdej6uskex8npajjqg.png)
Answer choice C is right.